2022
DOI: 10.1021/acs.jafc.2c00479
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with rac-GR24 Facilitates the Accumulation of Biomass and Astaxanthin in Two Successive Stages of Haematococcus pluvialis Cultivation

Abstract: The unicellular freshwater green alga Haematococcus pluvialis has attracted much research attention due to its biosynthetic ability for large amounts of astaxanthin, a blood-red ketocarotenoid that is used in cosmetics, nutraceuticals, and pharmaceuticals. Recently, numerous studies have investigated the functions of natural astaxanthin; however, the high cost of the production of astaxanthin from H. pluvialis cultures restricts its commercial viability. There is an urgent need to fulfill commercial demands by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…The CO 2 utilization efficiency of P. tricornutum cultures was assessed using 500 mL Duran laboratory bottles with stainless steel two-port connector gaps and calculated based on the input and output quantities of CO 2 using gas chromatography (Shimadzu, Japan). Furthermore, for enzyme extraction, the centrifuged P. tricornutum pellets were ground in liquid nitrogen with the pre-mixed solutions and the activities of two representative enzymes involved in photosynthesis, namely ribulose-1,5-bisphosphate carboxylase-oxygenase (RuBisCO) and carbonic anhydrase, were measured following previously reported protocols [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The CO 2 utilization efficiency of P. tricornutum cultures was assessed using 500 mL Duran laboratory bottles with stainless steel two-port connector gaps and calculated based on the input and output quantities of CO 2 using gas chromatography (Shimadzu, Japan). Furthermore, for enzyme extraction, the centrifuged P. tricornutum pellets were ground in liquid nitrogen with the pre-mixed solutions and the activities of two representative enzymes involved in photosynthesis, namely ribulose-1,5-bisphosphate carboxylase-oxygenase (RuBisCO) and carbonic anhydrase, were measured following previously reported protocols [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…3D). Apart from the alleviation function of NADPH to oxidative stress, NADPH also exhibited a major reducing equivalent for the biosynthesis of microalgae-based metabolites [19]. Based on these data, thus, it is assumed that the increase of ATP and NADPH stimulated by glycerol may provide enough reducing equivalents for concurrently alleviating oxidative damage and improving microalgae-based products.…”
Section: Molecular Responses Of H Lacustris Provided Preliminary Inte...mentioning
confidence: 99%
“…Previous studies have demonstrated that molecular analyses of microalgae could reveal the potential mechanism of responses by numerous treatments [19,31]. As shown in Fig.…”
Section: Molecular Responses Of H Lacustris Provided Preliminary Inte...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular biomass was determined following the protocol reported by Li et al (2019) [24]. Growth curve was generated by the direct count method and photosynthetic e ciency including maximal photochemical e ciency (Fv/Fm), relative electron transport rate (rETR), and non-photochemical quenching (NPQ) were measured by a pulse amplitude-modulated (PAM) uorometer (Water-PAM uorometer, Germany) described previously [25].…”
Section: Analysis Of Growth and Photosynthetic Activitymentioning
confidence: 99%